Importância da glicemia capilar após teste de sobrecarga com 50g de glicose na avaliação da macrossomia fetal - Claudia da Silva Folly (2006)
Objective: To evaluate if it is possible to predict the fetal macrosomia for the capillary glucose after 50 g glucose challenge test in normoglycemic gestations and the effect of capillary glucose levels in birth weight . Methods: This study prospectively evaluated 654 pregnant women with gestational age 20 weeks, proceeding from the Prenatal Service of the Caratingas Municipal Polyclinic. They were submitted to the screening test with 50 g of glucose, using capillary glucose, with the cut-off point of 140 mg/dl. The patients with positive screening (capillary glucose one hour after 50g 140mg/dl) were submitted to TOTG with 100g ofglucose and the result was considered positive for gestational diabetes mellitus when two or more values of glicemia were cut-off point established by the NDDG (105, 190, 165 and 145mg/dl). The pregnant women with DMG were excluded from the analysis. The following items from the protocol were analyzed: weight, height, IMC, age, gestational age (calculated from the date of the last menstruation), familiar history of diabetes in relatives of first degree and previous gestational history of thepregnant women (parity, gestational diabetes, newborn >4Kg, stillborn). In the end of gestations the neonatal results were evaluated (gestational age at birth, sex, weight - kg, stature - cm, cephalic perimeter - cm, thoracic perimeter - cm, type of delivery). Macrosomia was defined as birth weight greater than the 90th percentile for gestational age. Analysis of variance, linear regression and multiple logistic regression were used to examine the effect of the capillary glucose on the mean of the birth weight and the risk for GIG newborn. The sensitivity and specificity of thecapillary glucose after 50 g glucose challenge test was calculated to predict GIG newborn. Also, the curve ROC (Receiver Operator Characteristic Curve) was calculated to choose a cut-off point for the test. Results: A significant relationship was found between the increase of the maternal glucose level and the mean birth weight adjusted for covariates (p<0,0001) and the percentage of newborn GIG (p<0,0001). For each 10mg/dl of increase in the value of the capillary glucose from the value of 140mg/dl there was an increase of 87,5g in the mean of the birth weight,after adjustment for covariates (p=0,001), and increased adjusted odds of GIG (adjusted odds ratio [OR] 1,85; IC 95% [IC] 1,30-2,63). The screening test with capillary glucose validated from the measure of the fetal weight for the gestational age had as the best cut-off point the value of 146,5mg/dl, with the sensitivity of 36% and specificity of 88,7%, and the area under curve ROC=0,620, showing that the test has little discriminatory power to predict macrosomia. Conclusion: The levels of the capillary glucose have independent association with the birth weight. However, the limitation of the screening test-50g must be considered to predict fetal macrosomia in normoglycemic gestations, since it can produce a high number of false-negative results (60.5%). This test has good accuracy to keep away the occurrence from GIG newborns, with 17% of false-positives.